2000
DOI: 10.1038/35022535
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystal phase transitions in suspensions of polydisperse plate-like particles

Abstract: Colloidal suspensions that form periodic self-assembling structures on sub-micrometre scales are of potential technological interest; for example, three-dimensional arrangements of spheres in colloidal crystals might serve as photonic materials, intended to manipulate light. Colloidal particles with non-spherical shapes (such as rods and plates) are of particular interest because of their ability to form liquid crystals. Nematic liquid crystals possess orientational order; smectic and columnar liquid crystals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
326
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 420 publications
(346 citation statements)
references
References 26 publications
16
326
0
4
Order By: Relevance
“…Starting from the materials used in the Buining method [42] to produce boehmite rods, Wierenga et al [56] discovered a synthesis route which yields well-formed hexagonal plate-like gibbsite crystals (diameter 100-200 nm and thickness 5-15 nm). Subsequently, van der Kooij & Lekkerkerker [57] succeeded in sterically stabilizing these gibbsite platelets by grafting a layer of low-molecular-weight PIB molecules onto their surface following the method of Buining & Lekkerkerker [36]. This novel model system of hard colloidal platelets was observed to phase-separate into an isotropic and a nematic LC phase [57].…”
Section: Colloidal Silica Rodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from the materials used in the Buining method [42] to produce boehmite rods, Wierenga et al [56] discovered a synthesis route which yields well-formed hexagonal plate-like gibbsite crystals (diameter 100-200 nm and thickness 5-15 nm). Subsequently, van der Kooij & Lekkerkerker [57] succeeded in sterically stabilizing these gibbsite platelets by grafting a layer of low-molecular-weight PIB molecules onto their surface following the method of Buining & Lekkerkerker [36]. This novel model system of hard colloidal platelets was observed to phase-separate into an isotropic and a nematic LC phase [57].…”
Section: Colloidal Silica Rodsmentioning
confidence: 99%
“…Subsequently, van der Kooij & Lekkerkerker [57] succeeded in sterically stabilizing these gibbsite platelets by grafting a layer of low-molecular-weight PIB molecules onto their surface following the method of Buining & Lekkerkerker [36]. This novel model system of hard colloidal platelets was observed to phase-separate into an isotropic and a nematic LC phase [57]. Upon further increasing the particle concentration, van der Kooij et al [58] observed that suspensions of these sterically stabilized plate-like gibbsite colloids also display a columnar phase (figure 4) in good agreement with the computer simulation results of Veerman & Frenkel [51].…”
Section: Colloidal Silica Rodsmentioning
confidence: 99%
“…The observed marble pattern, with various interference colors due to the birefringence of the sample, is characteristic of liquid crystalline phases. [21,22] Although we have not identified the type of liquid crystal, lamellar, [28] and columnar, [31] as well as nematic phases, can occur for the present nanosheet colloid.The liquid crystalline state of the niobate nanosheets is highly stable. We observed birefringence even at the concentration of 5 10 ±5 mol dm ±3 or ca.…”
mentioning
confidence: 99%
“…These observations provided, in part, the experimental stimulus for the theory put forward by Onsager [1]. However, it took more than half a century before further experimental evidence for liquid crystal phase equilibria in suspensions of plate-like particles was obtained [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%